Peningkatan Kemampuan Guru Dalam Menyusun Soal Computer Based Test Melalui In-House Training - Slamet Utomo (LPMP Provinsi DKI Jakarta, 2021)
Computer Based Test (CBT) plays an important role to support efficient and faster formative and summative evaluations conducted by teachers in schools. The purpose of this research is to improve the teacher's ability in preparing CBT questions. The research was conducted at SMA Islam Cikal Harapan 2 for the 2019/2020 academic year involving 10 teachers. The type of this research is a school action research (PTS), two cycles, with stages of planning, implementation, observation, and reflection. Collecting data using the technique of questionnaires, documentation and tests. The results of the study revealed that the percentage of teachers' ability to create CBT questions increased from 60% in the first cycle to 87% in the second cycle. These abilities include preparing questions, creating supporting files, and uploading questions on a computer. In addition, teacher activity in IHT increased from 73% in cycle I to 87% in cycle II. The conclusion of this research is that the ability to create CBT questions and teacher activities can be improved through in-house training.